2010
DOI: 10.3168/jds.2009-2552
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate source and protein degradability alter lactation, ruminal, and blood measures

Abstract: Thirty-eight lactating dairy cows including 6 ruminally cannulated cows were used in a feeding study to assess effects of feed sources that differed in dietary nonfiber carbohydrate (NFC) composition and ruminal degradability of dietary protein (RDP) on production, ruminal, and plasma measures. The design was a partially balanced, incomplete Latin square with three 21-d periods and a 3 x 2 factorial arrangement of treatments. Samples and data were collected in the last 7 d of each period. Feed sources that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
6
34
0
2
Order By: Relevance
“…Dietary non-fibre carbohydrates (NFC) are the major source of energy for high-producing dairy cattle, providing 30 to 45% of the diet on a dry matter (DM) basis (Hall et al, 2010). They are a very diverse group of carbohydrates, which include starch, sugars, fructans, and pectic substances (Hall, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary non-fibre carbohydrates (NFC) are the major source of energy for high-producing dairy cattle, providing 30 to 45% of the diet on a dry matter (DM) basis (Hall et al, 2010). They are a very diverse group of carbohydrates, which include starch, sugars, fructans, and pectic substances (Hall, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary carbohydrate is composed of neutral detergent fibre (NDF) and non-fibre fractions, which collectively compose 65% to 75% of the diets of lactating dairy cattle. Non-fibre carbohydrates (NFC) may provide 30 to 45% of the diet on a dry matter (DM) basis (Hall et al, 2010). Root crops such as potato have been used in dairy rations, but have been replaced by grains and maize silage because of labour costs (Eriksson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lupin seed DM and CP are more susceptible to the degradation process in the rumen environment of cows receiving diets containing sucrose compared with susceptibility in the rumen of cows receiving diets containing starch, as indicated by higher degradation values estimated after 8 h and 16 h of incubation (P < 0.05), higher rate of degradation of insoluble but potentially degradable fractions (P < 0.05), and higher eff ective degradability (P < 0.05) corrected for the particle loss. Th e results obtained as well as the fi ndings of Hall et al (2010) indicated that the type of non-fi bre carbohydrates can interact with the soluble dietary N fraction to give diff erent directions of response for ruminal fermentation. Th e crude protein of experimental diets contained 34% of the non-protein N fraction derived from grass silage.…”
Section: Discussionmentioning
confidence: 85%